ChemInform Abstract: Nano‐Fe3O4 Encapsulated‐Silica Particles Bearing 3‐Aminopropyl Group as a Magnetically Separable Catalyst for Efficient Knoevenagel Condensation of Aromatic Aldehydes with Active Methylene Compounds. Issue 42 (14th October 2014) - Liu, Shuo; Ni, Yuxiang; Yang, Jianguo; Hu, Huanan; Ying, Anguo; Xu, Songlin
Abstract The preparation of a new 3‐aminopropyl‐functionalized Fe3O4/SiO2 catalyst is described which is used for the Knoevenagel condensation of aromatic aldehydes with active methylene compounds.